Development and Feasibility Testing of CATCH Healthy Smiles, an Oral Health Promotion Intervention for Prevention of Dental Caries Among Elementary School Children. (17th November 2021) - Sharma, Shreela V.; Kelder, Steven; Yamal, Jose‐Miguel; Chuang, Ru‐Jye; Byrd‐Williams, Courtney; Bona, Gisela; Bajaj, Nimit; Brito, Frances; Neumann, Ana S.
ABSTRACT: BACKGROUND: We present results of the development and feasibility testing of CATCH Healthy Smiles, a school‐based oral health program, among children in grades K‐2 in Houston, Texas. METHODS: Study design was cross‐sectional (N = 2 schools; N = 125 parent‐child dyads; 31 kindergarteners, 42 first graders, and 52 second graders). CATCH Healthy Smiles program was implemented by trained school teachers in the 2016‐2017 school year. Trained dentists conducted dental assessments to measure dental caries increment score (d3mfs). Parent‐reported 24‐hour dietary recalls and surveys assessed child and parent behavioral, environmental, and psychosocial factors. Logistic regression analysis assessed factors associated with caries experience adjusting for covariates. RESULTS: Of the 113 children with complete dental assessments, 54% children in grade K, 62% in first grade, and 73% in second grade had caries experience. Children with caries experience had a higher body weight (AdjOR = 1.13, 95% confidence interval [CI]: 1.02‐1.29), were less likely to be girls (AdjOR = 0.22, 95% CI: 0.05‐0.82), had greater odds of difficulty drinking hot or cold beverages because of dental problems (AdjOR = 13.13, 95% CI: 1.09‐275.14), greater frequency of consuming sugar‐sweetened beverages (AdjOR = 11.53, 95% CI: 2.10‐87.19), greater odds of receiving government assistance (AdjOR = 14.62, 95% CI: 2.74‐119.81), and lower odds of seeing a dental provider (AdjOR = 0.11, 95% CI: 0.02‐0.45). Process evaluation showed that 100% of the CATCH Healthy Smiles lessons and activities were taught in the two schools with a high degree of program fidelity and acceptability across the schools, children, and parents. CONCLUSIONS: These data will be used to conduct a subsequent fully powered cluster randomized controlled trial.